(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: Application Of Cooperative Learning Model Type Of Discovery Learning In Increasing Science Learning Outcomes In Class IV Students SD Negeri 241 Palembang. The purpose of this action research is to determine the increase in student learning outcomes after the implementation of the Discovery Learning Type Cooperative Learning Model. This study uses two rounds of action research (classroom action research). Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The location of this classroom action research was carried out at SD Negeri 241 Palembang, South Sumatra province. This research was conducted from February to April 2019 for the 2018/2019 academic year. The subjects of this study were students of class IV.A SD Negeri 241 Palembang, totaling 30 students. The main topic of discussion was about the material "Energy and Its Use". The data obtained were in the form of formative test results, observation sheets for teaching and learning activities and documentation. From the results of the analysis, it was found that the learning outcomes of students experienced a significant increase marked by an increase in students’ learning mastery in each cycle, namely pre-cycle (21.88%), cycle I (66.67%) and (86.67%) in cycle II. The conclusion of this study is that the cooperative learning model of the Discovery Learning type can have a positive effect on the learning outcomes of students at SD Negeri 241 Palembang, and this learning model can be used as an alternative in efforts to improve science learning. Keywords: Learning Outcomes, cooperative learning model type Discovery Learning, IPA Abstrak: Penerapan Model Pembelajaran Kooperatif Tipe Discovery Learning Dalam Meningkatkan Hasil Belajar IPA Pada Siswa Kelas IV SD Negeri 241 Palembang. Tujuan dari penelitian tindakan ini adalah untuk mengetahui peningkatan hasil belajar peserta didik setelah diterapkannya Model Pembelajaran Kooperatif Tipe Discovery Learning. Penelitian ini menggunakan penelitian tindakan (classroom action research) sebanyak dua putaran. Setiap putaran terdiri dari empat tahap yaitu: rancangan, kegiatan dan pengamatan, refleksi, dan revisi. Lokasi penelitian tindakan kelas ini dilaksanakan di SD Negeri 241 Palembang, provinsi Sumatera Selatan. Penelitian ini dilaksanakan pada Februari s/d April 2019.Subjek penelitian ini adalah peserta didik kelas IV.A SD Negeri 241 Palembang yang berjumlah 30 peserta didik. Pokok bahasan yang disampaikan mengenai materi œEnergi dan Penggunaannya.Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar dan dokumentasi. Dari hasil analis didapatkan bahwa hasil belajar peserta didik mengalami peningkatan yang signifikan ditandai dengan peningkatan ketuntasan belajar peserta didik dalam setiap siklusnya, yaitu pra siklus (21.88 %),siklus I (66.67%) dan (86.67%) pada siklus II. Kesimpulan dari penelitian ini adalah model pembelajaran kooperatif tipe Discovery Learning dapat berpengaruh positif terhadap hasil belajar peserta didik SD Negeri 241 Palembang, serta model pembelajaran ini dapat digunakan sebagai salah satu alternatif dalam upaya perbaikan pembelajaran IPA. Kata Kunci: Hasil Belajar, model pembelajaran kooperatif tipe Discovery Learning, IPA